(untitled) (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2025)
This study investigates the relationship between adult literacy and health-promoting behaviors in rural communities of Cross River State, Nigeria, where low literacy and poor health outcomes persist. Despite global evidence linking literacy to better health practices, rural Nigeria faces challenges like limited access to education and healthcare. Using a descriptive survey design, data were collected via questionnaires from 400 adults aged 18–60 across 10 rural communities in Ogoja and Obudu Local Government Areas. Findings show that 58% of participants had basic literacy skills, but only 42% engaged in consistent health-promoting behaviors like regular medical check-ups or balanced diets. Literacy levels significantly correlated with health practices (r = 0.67, p < 0.05), with higher literacy linked to better hygiene and preventive care. Barriers included inadequate health education (75%) and limited access to healthcare facilities (82%). Qualitative insights revealed cultural beliefs and economic constraints as additional hurdles. The study recommends integrating literacy programs with health education, leveraging community-based interventions, and improving healthcare infrastructure. These findings underscore the transformative potential of literacy in fostering health-promoting behaviors, offering a pathway to enhance rural well-being.